Effects of Different Chainring Designs on Cycling Performance: Oval Versus Circular - Fatih KOÇAK; Salih PINAR; Hayri ERTAN (ümit doğan üstün, 2024)
Professional road cycling requires high endurance and power output for optimal performance. Oval chainrings, a recent innovation, aim to minimize dead spots during pedal revolutions and enhance cycling performance. This study compared the effects of circular (C-ring) and oval (Q-ring) chainrings on power output and maximum oxygen consumption (V·O2Max) during an incremental exercise test. Twenty male elite cyclists (mean age ± SD: 19.90 ± 1.86 years) participated in a randomized study. They underwent two incremental maximal tests separated by 48 hours, using both chainring types. The test began with participants pedaling with a 200-watt load in their preferred cadence. During the first six-minute period, the load was increased by 50 watts every two minutes, and then the test continued to increase by 25 watts every two minutes. The test was completed at the point where the participant was exhausted. The results indicated significant differences in favor of Q-rings for V·O2Max (p = 0.006) and power output (p = 0.014), while heart rate and cadence remained similar. High correlations were found between V·O2Max/power output and heart rate mean/max. Linear regression analysis revealed that power output accounted for 52% (Q-ring) and 64% (C-ring) of the variance in V·O2Max. Theoretical advantages of Q-rings include optimizing pedal force distribution, which may enhance mechanical performance. Previous studies have shown mixed results regarding the effects of non-circular chainrings on cycling performance, indicating methodological disparities. Overall, this study suggests that Q-rings may improve road cycling performance by increasing power output. However, further research is needed to explore their efficacy across various cycling scenarios.